HUBUNGAN KEBIASAAN MINUM SUSU FORMULA MENGGUNAKAN BOTOL (DOT) TERHADAP KEJADIAN KARIES GIGI PADA ANAK USIA 2-3 TAHUN DI PAUD DESA KEDUNGJATI BALEREJO KABUPATEN MADIUN - Yuliana, Fitria; Wahyuning, Binar; Betty, Sesaria; Fika, Yudha (Jurnal Biogenerasi, 2024)
The aim of this research was to determine the relationship between the habit of drinking formula milk using bottles (DOT) and the incidence of dental caries in children aged 2-3 years at PAUD Mutiara Madiun. The research design used in this research is correlative analytics and this research uses a cross-sectional approach. The population in this study was 38 children. The sample in this study was 35 children with the sampling technique used in this study being simple random sampling. This study uses Kendall's tau analysis to test the relationship between the two variables. The results of the analysis using the Kendall's tau_b statistical test showed that the ρ-value was 0.000 α 0.05, which means that H1 was accepted, meaning there was a relationship between the habit of drinking formula milk using a bottle (pacifier) ​​and the incidence of dental caries in children aged 2-3 years in PAUD, Kedungjati Village, Balerejo Regency. Madiun. The closeness of the relationship can be seen from the Correlation Coefficcent -0.772, which means it is in the strong correlation range.